Effect of the gel elasticity of model skin matrices on the distance/depth‐dependent transmission of vibration energy supplied from a cosmetic vibrator. (28th June 2016) - Jeong, M. K.; Hwang, C.; Nam, H.; Cho, Y. S.; Kang, B. Y.; Cho, E. C.
Abstract: Objective: The purpose of this study was to determine how the energies supplied from a cosmetic vibrator are deeply or far transferred into organs and tissues, and how these depths or distances are influenced by tissue elasticity. Methods: External vibration energy was applied to model skin surfaces through a facial cleansing vibrator, and we measured a distance‐ and depth‐dependent energy that was transferred to model skin matrices. As model skin matrices, we synthesized hard and soft poly(dimethylsiloxane) (PDMS) gels, as well as hydrogels with a modulus of 2.63 MPa, 0.33 MPa and 21 kPa, respectively, mostly representing those of skin and other organs. The transfer of vibration energy was measured either by increasing the separation distances or by increasing the depth from the vibrator. Results: The energies were transmitted deeper into the hard PDMS than into the soft PDMS and hydrogel matrices. This finding implies that the vibration forces influence a larger area of the gel matrices when the gels are more elastic (or rigid). There were no appreciable differences between the soft PDMS and hydrogel matrices. However, the absorbed energies were more concentrated in the area closest to the vibrator with decreasing elasticity of the matrix. Softer materials absorbed most of the supplied energy around the point of the vibrator. In contrast, harder materials scattered the external energy over a broad area. Conclusions: The current results are the first report in estimating how the external energy is deeply or distantly transferred into a model skins depending on the elastic moduli of the models skins. In doing so, the results would be potentially useful in predicting the health of cells, tissues and organs exposed to various stimuli. Abstract : The purpose of this study was to determine how the energies supplied from a cosmetic vibrator are deeply or far transferred into model skin matrices, and how these depths or distances are influenced by elasticity of matrices. External vibration energy supplied from a facial cleansing vibrator is differentially transferred depending on the elastic modulus of the model skin matrix. Résumé: Objectif: Le but de cette étude est de déterminer comment les énergies fournies par un vibrateur cosmétique sont transférées soit en profondeur soit latéralement dans les organes et les tissus, et comment ces profondeurs ou les distances sont influencées par l'élasticité des tissus. Methodes: De l'énergie de vibration externe a été appliquée sur des surfaces de modèles de peau à l'aide d'un vibrateur de nettoyage du visage, et nous avons mesuré une énergie dépendante de la distance et de la profondeur qui a été transférée aux modèles de la matrice de la peau. En tant que modèle des matrices de la peau, nous avons synthétisé des gels de poly (diméthylsiloxane) (PDMS) dur et mou, ainsi que des hydrogels ayant un module de 2, 63 MPa, 0, 33 MPa et 21 kPa, respectivement, pour la plupart représentant ceux de la peau et d'autres organes. Le transfert de l'énergie vibratoire a été mesuré soit en augmentant les distances de séparation ou en augmentant la profondeur par rapport au vibrateur. Résultats: Les énergies ont été transmises plus profondément dans les PDMS dures que dans les PDMS mous et des matrices d'hydrogel. Cette constatation implique que les forces de vibration influencent une plus grande surface des matrices de gel lorsque les gels sont plus élastiques (ou rigide). Il n'y avait pas de différence notable entre les PDMS mous et des matrices d'hydrogel. Cependant, les énergies absorbées sont plus concentrées dans la zone la plus proche du vibreur avec la diminution de l'élasticité de la matrice. Les matériaux plus mous absorbent plus de l'énergie fournie autour du point du vibrateur. En revanche, des matériaux plus durs dispersent l'énergie externe sur une large zone. Conclusions: Les résultats actuels sont le premier rapport dans l'estimation de la façon dont l'énergie externe est transférée en profondeur ou latéralement dans un modèle de peau en fonction des modules d'élasticité. Ce faisant, les résultats seraient potentiellement utiles pour prédire la santé des cellules, des tissus et des organes exposés à divers stimuli.